Effect of heat stabilizer content on the gel characteristic of the modified-recycled PET for 3D printing filament application - Parneam Nismar; Na Ayutthaya Siriorn Isarankura; Sukhawipat Nathapong (E3S Web of Conferences)
This research identified the type of gel in the modified-recycled poly (ethylene terephthalate) (modified-rPET) filament, with various content of heat stabilizer, Pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate. The content of the heat stabilizer used in this study were 0, 0.05, 0.1, 0.2, 0.3, 0.4 and 0.5 pph. Gel characteristics of the modified-rPET filament were characterized by using the hot stage microscopy technique. It was found that gels with heat stabilizer at 0-0.3 pph showed the unmeltgel formation characteristic. On the other hand, the addition of heat stabilizer at 0.4-0.5 pph showed the formation of crosslinked-gel characteristic, this gel does not melt even if the temperature reached to the melting temperature. This gel affects the process-ability of 3D printing. Therefore, it becomes clogged at the nozzle of 3D printer. Furthermore, this research also determined the crosslinked-gel contents inside the modified-rPET filaments, with various content of heat stabilizer, by a solvent extraction technique. Using trifluoroacetic acid/dichloromethane blended solution, it was found that at increase of the heat stabilizer content, the higher the content of crosslinked gel were observed significantly.